Structural change and relative demand for skilled workers: new evidence from the US manufacturing. (10th June 2019) - Chongvilaivan, Aekapol; Hur, Jung
Abstract: The present paper empirically investigates the effects of structural change—change in labor productivity fueled by labor reallocation across industries—on relative demand for skilled workers, using the NBER-CES Manufacturing Industry Database for the period of 1958–2011. The measures unveil that the US manufacturing sectors had experienced dramatic structural change since the 1990s when labor was reallocated from high-productivity to low-productivity industries. Furthermore, we find the evidence that the growth-reducing structural change impinges positively on relative demand for skilled workers and is therefore another driving force of rising wage inequality, apart from high-tech capital investment and outsourcing activities, in the US manufacturing sectors.